Pediatric blunt pancreatic trauma at a single center in Korea: a retrospective review from 2007 to 2022 - Joong Kee Youn; Hee-Beom Yang; Dayoung Ko; Hyun-Young Kim (Journal of Trauma and Injury)
Purpose Blunt pancreatic trauma in pediatric patients is relatively rare, yet it is associated with high risks of morbidity and mortality This study aimed to review pediatric patients with blunt pancreatic trauma treated at a single center and provide treatment guidelines. Methods This study included patients under the age of 18 years who visited our center's pediatric emergency department and were diagnosed with pancreatic injury due to abdominal trauma via radiological examination between January 2007 and December 2022. Patients’ medical records were retrospectively reviewed and analyzed. Results Among 107 patients with abdominal trauma, 14 had pancreatic injury, with a median age of 8.2 years (interquartile range, 3.1–12.3 years). Eight patients were male and six were female. The most common mechanism of injury was falls from a height and bicycle handlebars (four cases each). Six patients had associated injuries. Two patients had American Association for the Surgery of Trauma grade I or II, eight had grade III, and four had grade IV or V injuries. Eight patients underwent surgical resection, and four were discharged with only an intervention for duct injuries. Conclusions Patients with blunt pancreatic trauma at our center have been successfully treated with surgical modalities, and more recently through nonsurgical approaches involving active endoscopic and radiologic interventions.